2022
DOI: 10.1177/17455057221096218
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of antioxidant therapy (vitamin C) in an experimentally induced mouse model of ovarian endometriosis

Abstract: Objectives: This study investigates the therapeutic effect of vitamin C on the development of endometrial lesions and fecundity disorders in the ovarian induction model of mouse endometriosis. Methods: Ovarian endometriosis was surgically induced in 14 NMRI female mice (treatment group, N = 7) and (control group, N = 7). Three days after the second surgery (to assess endometriotic implant), the mice were randomized into two intervention groups: control (placebo) and treatment (50 mg/kg vitamin C every two days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, increasing evidence from animal studies indicates the inhibitory effect of vitamin C supplementation on lesions associated with endometriosis [ 34 , 35 , 36 , 37 ]. In such experiments, investigators used various parameters to describe the appearance of ectopic endometrial tissue, such as the size, volume, and mass of the lesions, as well as various assessments related to associated adhesions, assessment of fibrosis, and the condition of the mucosa associated with the lesion epithelium.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing evidence from animal studies indicates the inhibitory effect of vitamin C supplementation on lesions associated with endometriosis [ 34 , 35 , 36 , 37 ]. In such experiments, investigators used various parameters to describe the appearance of ectopic endometrial tissue, such as the size, volume, and mass of the lesions, as well as various assessments related to associated adhesions, assessment of fibrosis, and the condition of the mucosa associated with the lesion epithelium.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“…In such experiments, investigators used various parameters to describe the appearance of ectopic endometrial tissue, such as the size, volume, and mass of the lesions, as well as various assessments related to associated adhesions, assessment of fibrosis, and the condition of the mucosa associated with the lesion epithelium. Although all authors consistently observed the inhibitory effect of vitamin C, which was reflected in a decrease in the above-mentioned parameters describing the lesions, the only parameter in all the analyzed studies that underwent significant changes in the groups supplemented with vitamin C was the volume of lesions [ 34 , 35 , 36 , 37 ].…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“…Hoorsan et al [ 115 ], based on their findings in mice, concluded that vitamin C could improve ovarian function and reduce the induction and growth of endometrial grafts. Similar conclusions were reached in a study on rats.…”
Section: Vitaminsmentioning
confidence: 99%
“…Hoorsan et al, in their experiment on mice, suggested that vitamin C has considerable importance for improving the fecundity function of ovaries and reducing the induction and growth of endometrial implants [44].…”
Section: Vitamins Cmentioning
confidence: 99%